Efeitos do ferro e da heterogeneidade de habitat na estrutura e biomassa das algas perifíticas - Santos, Ranyelle Caretta (2022)
Water resources are essential ecosystems for living beings, but they have been subjected to pollutants from various sources. Heavy metals are one of the main known sources of pollution, discharged via effluents and, as seen more recently in Brazilian rivers, due to the rupture of mining tailings dams. Among metals, iron is an element that plays an important role in the composition of essential macromolecules of living organisms, as long as it is in adequate concentrations. The high concentration of iron in aquatic environments has become a problem, affecting the organization of biological communities. Periphytic algae are important mediators of anthropogenic impacts, being able to accumulate various nutrients, including metals, reflecting changes in the characteristics of the community. They are also influenced by spatial heterogeneity and complexity, which can help the community resist environmental impacts, since more complex habitats provide a greater range of niches and microenvironments that can be colonized, harboring greater diversity and richness. The hypothesis guiding this research is that more heterogeneous and complex habitats will provide greater resistance to periphytic algae impacted by high iron concentrations, since more heterogeneous and complex habitats will support greater richness, diversity and presence of tolerant algal species, due to the greater number of microhabitats and niches available to be occupied. The objective of this study was to evaluate the effect of iron and different degrees of habitat complexity on the structure and biomass of periphytic algae. For this purpose, periphytic algae were maintained in microcosms with different degrees of heterogeneity for thirty days, in two groups (positive: with added iron; control: culture medium without added iron), containing 6 treatments worked in triplicate. To create the different degrees of heterogeneity (treatments), macrophytes with different characteristics were used: a) submerged macrophyte (Egeria sp.), and b) floating macrophytes (Salvinia auriculata and Landoltia sp.). The periphyton inserted in the mesocosms was cultivated on artificial substrates from propagules collected in lentic environments of Lagoa Encantada and lower Rio Doce. The periphytic algae were evaluated by the following attributes: taxonomic composition, richness, density, dry weight, ash-free dry weight, pigments, dominance and abundance. To relate the ecophysiological changes in the algal community with the environmental variables, the nitrate and orthophosphate of the water, nitrogen, phosphorus and iron of the periphyton and macrophytes when possible were determined. The results obtained were evaluated using descriptive statistics, analyzing the amplitude of data variation and the dispersion around the mean. To give statistical rigor to the groups formed, the multiparametric statistical test PERMANOVA was applied. There was no interaction between habitat heterogeneity and iron. There was no significant difference in the community attributes regarding either habitat heterogeneity or iron addition. Diatoms were the most abundant in both groups and were resistant to the chemical stress generated by the addition of iron. A total of 82 taxa were recorded, distributed in 9 classes and 1 unidentified group (phytoflagellate). The number of indicator species was low, corresponding to 10% of the total number of taxa, so that the positive group presented 5 species and the control group 3. The concentration of iron added to the positive group was sufficient to generate significant changes in the composition of the periphytic community and did not result in significant losses in the community biomass. The macrophytes Salvinia auriculata and Landoltia sp. were shown to be good iron sequestrators from water and can be used as allies in bioremediation projects. The hypothesis was rejected, since no significant responses of the periphytic community were observed in relation to the different heterogeneities worked in the mesocosms.